Peran Kepuasan Kerja Dalam Mediasi Pengaruh Kualitas Kehidupan Kerja Terhadap Kinerja Pegawai : Studi Pada Pegawai Kantor Kecamatan Lowokwaru Kota Malang - Meliana Herliance Oes; Survival Survival; Nasharuddin Mas (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the effect of quality of work life on employee performance with job satisfaction as a mediating variable for employees at the Lowokwaru District Office, Malang City. Quality of work life is one of the important factors that can influence employee satisfaction and performance in a bureaucratic work environment. This study uses a quantitative approach with an explanatory research type to explain the causal relationship between variables. The population in this study were all 37 employees of the Lowokwaru District Office, and all of them were used as research samples through a total sampling technique. Data collection techniques were carried out through distributing questionnaires, direct interviews, and observations to obtain more comprehensive and in-depth data. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Square (SmartPLS) to test the structural model and research hypotheses. The results showed that quality of work life had a positive and significant effect on job satisfaction and employee performance. Job satisfaction was also proven to have a positive and significant effect on employee performance. In addition, job satisfaction was proven to significantly mediate the relationship between quality of work life and employee performance. Thus, these findings reinforce the importance of creating a supportive, fair work environment that provides a work-life balance to enhance job satisfaction and encourage overall employee performance. The implications of this research suggest that government agency management, particularly at the sub-district level, needs to prioritize efforts to improve the quality of work life as a strategy to encourage optimal employee performance. Improving aspects such as working conditions, participation in decision-making, career development, and work-life balance should be prioritized in managerial policies.